2007
DOI: 10.1158/0008-5472.can-06-2875
|View full text |Cite
|
Sign up to set email alerts
|

TSC1 Sets the Rate of Ribosome Export and Protein Synthesis through Nucleophosmin Translation

Abstract: Nucleophosmin (B23) is a nucleolar phosphoprotein that has been implicated in numerous cellular processes. In particular, nucleophosmin interacts with nucleolar components of newly synthesized ribosomes to promote ribosome nuclear export. Nucleophosmin is a classic mitogen-induced protein, with changes in its expression correlating with growth factor stimulation. In this study, we examined the underlying mechanism of nucleophosmin induction and showed that hyperproliferative signals emanating from oncogenic H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 49 publications
3
35
1
Order By: Relevance
“…Furthermore, we show that NPM expression is regulated by mTOR, as mTOR inhibition by rapamycin inhibits NPM expression both in vitro and in vivo. This supports previous studies showing that NPM is highly expressed in TSC1 À/À fibroblasts and is blocked by rapamycin treatment (27).…”
Section: Expression Of Npm Is Regulated By Mtor In Nf1supporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, we show that NPM expression is regulated by mTOR, as mTOR inhibition by rapamycin inhibits NPM expression both in vitro and in vivo. This supports previous studies showing that NPM is highly expressed in TSC1 À/À fibroblasts and is blocked by rapamycin treatment (27).…”
Section: Expression Of Npm Is Regulated By Mtor In Nf1supporting
confidence: 92%
“…Expression of a NPM mutant that is unable to shuttle from the nucleus to the cytoplasm blocks ribosomal export (26). In addition, treatment with rapamycin inhibits NPM protein expression in MEFs (27). In Nf1 À/À astrocytes, we also found that mTOR inhibition by rapamycin dramatically reduced NPM expression in Nf1 À/À astrocytes with no effect on wild-type astrocytes (Fig.…”
Section: Expression Of Npm Is Regulated By Mtor In Nf1mentioning
confidence: 54%
See 2 more Smart Citations
“…123 Indeed, one of the major targets of mTORC1 signaling is the nucleophosmin (NPM) proto-oncogene, a TOP-containing mRNA. Growth signals, such as those emanating from RAS, stimulate the translation of existing NPM mRNAs in a rapamycin-sensitive mechanism 124 through the binding of far upstream binding protein-1 (FUBP-1) to the 3' untranslated region (UTR) of NPM mRNA. 125 In agreement with this finding, astrocytes lacking Nf1 express elevated NPM protein levels and exhibit enhanced protein synthesis.…”
Section: Downstream Mtor Signalingmentioning
confidence: 99%